Determination of methyldopa in pharmaceutical formulations by combined spot test-diffuse reflectance spectroscopy - Ribeiro, Paulo Roberto S. [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (FapUNIFESP (SciELO), 2006)
This paper describes a very simple and rapid quantitative reflectance spot test procedure for the determination of methyldopa in pharmaceutical formulations. This method is based on the complexation reaction of methyldopa with molybdate ions yielding a yellow stable complex on filter paper. Reflectance measurements were carried out at 410 nm. Under optimal conditions, the calibration graphs obtained for methyldopa by plotting the optical density of the reflectance signal (A R) vs. the log of the concentration were linear from 6.30 × 10 -3 to 1.89 × 10 -2 mol L -1, with a correlation coefficient of 0.998. The detection limit was 2.74 × 10 -3 mol L -1 (R.S.D. = 1.02%) for methyldopa. The common excipients used as additives in pharmaceuticals do not interfere in the proposed method. The method was applied to determine metyldopa in commercial pharmaceutical formulations. The results obtained by the proposed method compare favorably with those obtained by an official procedure at 95% confidence level. ©2006 Sociedade Brasileira de Química.
Keywords: Diffuse reflectance; Methyldopa; Pharmaceuticals formulations